(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
This article provides an in-depth analysis of the theoretical foundations of pottery technology and modern compositional solutions. During the study, the historical development of pottery, technological methods and materials in different regions were studied. The influence of compositional factors such as shape, color, texture and decorative elements on the artistic and functional quality of the product was also highlighted. Based on practical experiments, the effectiveness of modern technologies, including 3D printing and high-temperature firing methods, was evaluated. At the end of the study, innovative approaches and promising directions in the field of pottery were identified.